The 13 treasures - Harrison, Michelle 1979- (Simon & Schuster, 2009)
50 years ago, a girl vanished in the woods nearby - a girl Tanya's grandmother will not speak of. Fabian, the caretaker's son, is tormented by the disappearance - his grandfather was the last person to see her alive. Together Tanya and Fabian decide to find the truth. Tanya has her own secret - she can see fairies ....Ages 13+